2016
DOI: 10.2106/jbjs.15.00845
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Investigation of Commonly Used Landmarks for Evaluating Rotation During Forearm Fracture Reduction

Abstract: This study, to our knowledge, represents the first anatomic investigation of the rotational profiles between the osseous landmarks used to assess forearm rotation after fracture. We recommend that surgeons first image the bicipital tuberosity at its largest profile, supinate the arm 20°, and confirm that the radial styloid is at its largest profile. The ulna can then be assessed to support the lack of rotational deformity in the forearm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Many previous studies have found variation in radial torsion angle among individuals but limited variation between sides of the same individual. 22,23,26,27 Despite this, a study by Dumont et al 25 noted some intra-individual side-to-side variation in normal volunteers, indicating that side-to-side comparison may not be as robust as originally believed. The lack of side-to-side comparison in the present retrospective study prevents us from assessing this.…”
Section: Discussionmentioning
confidence: 97%
“…Many previous studies have found variation in radial torsion angle among individuals but limited variation between sides of the same individual. 22,23,26,27 Despite this, a study by Dumont et al 25 noted some intra-individual side-to-side variation in normal volunteers, indicating that side-to-side comparison may not be as robust as originally believed. The lack of side-to-side comparison in the present retrospective study prevents us from assessing this.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, the rotation of both forearm bones is subject to scatter within the population, with the ulna varying by >50°. 13 , 17 Landmarks that appear to be easily detected on conventional x-rays and are commonly used for rotational evaluation, such as the bicipital tuberosity or the radial styloid, may only be used to a very limited extent because of high natural variation among the population. 17 As a result, examining the rotational displacement of the fragments using conventional x-ray images is extremely difficult and likely has an underestimated rate of inaccuracy.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the necessity of our data and the need for correct rotational placement of the prosthesis. We are therefore convinced that a preoperative CT scan of the whole forearm will be unavoidable to obtain the correct rotational implantation of the prosthesis with its offset, since distal landmarks, for example, the ulnar styloid, can only be used as a constant landmark to a very limited extent [ 19 ].…”
Section: Discussionmentioning
confidence: 99%